2011
DOI: 10.1016/j.jvs.2011.03.262
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of neck bleeding after eversion carotid endarterectomy

Abstract: The results of this single-center university hospital study show that neck bleeding after CEA is relatively common but is not associated with an increased risk of stroke or death. Preoperative treatment with clopidogrel, particularly when it is continued to the day before surgery, and postoperative arterial hypertension seem to be associated with a higher risk of neck bleeding after CEA, requiring re-exploration in most cases. Other antiplatelet agents appear to be associated with an increased risk of postoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 34 publications
3
35
0
Order By: Relevance
“…17 Of interest was the fact that the risk of severe neck bleeding after CEA requiring reoperation was higher in patients who received clopidogrel as a single chronic antiplatelet agent (7.8%) and also in patients who received clopidogrel 24 hours before surgery (9.5% vs. 4.7%) in our series. This finding is not new, and demonstrates the relationship previously reported, as in Baracchini et al, 11 where the risk of reoperation in patients treated with clopidogrel until the day before surgery was 15 times higher. Contrary to our results, the double antiplatelet treatment was associated with an increased incidence of bleeding in Rosenbaum et al 14 and reported the highest rate of bleeding in the group of patients who received clopidogrel over ASA.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…17 Of interest was the fact that the risk of severe neck bleeding after CEA requiring reoperation was higher in patients who received clopidogrel as a single chronic antiplatelet agent (7.8%) and also in patients who received clopidogrel 24 hours before surgery (9.5% vs. 4.7%) in our series. This finding is not new, and demonstrates the relationship previously reported, as in Baracchini et al, 11 where the risk of reoperation in patients treated with clopidogrel until the day before surgery was 15 times higher. Contrary to our results, the double antiplatelet treatment was associated with an increased incidence of bleeding in Rosenbaum et al 14 and reported the highest rate of bleeding in the group of patients who received clopidogrel over ASA.…”
Section: Discussionsupporting
confidence: 89%
“…Also, the relationship found in the univariate analysis between postoperative hypertension and cervical bleeding supported the results of previous publications, where postoperative hypertension nonresponding to therapy is associated with a higher rate of reoperation because of bleeding. 11,17 In our experience the cervical bleeding and early reoperation did not result in increased morbidity and mortality, according to other publications, 11,17 but this is a potentially serious complication. In other studies, this complication increase not only the risk of mortality 8,13,16 but also of stroke 13,16 and myocardial infarction.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…1 Drs Stone, Goodney, and Nolan believe that the number of our patients continuing clopidogrel (n ϭ 110) or aspirin (n ϭ 95) or both (n ϭ 10) to the day before carotid endarterectomy (CEA) is too small to draw any definite conclusions about the risk of neck bleeding after CEA. Since our preoperative protocol includes the discontinuation of any type of preoperative antiplatelet therapy for 1 week before surgery, it was already expected that only a small percentage of patients would violate this protocol, mainly for their own omission.…”
Section: Replymentioning
confidence: 95%
“…
We noted with interest the recent study by Baracchini et al,1 which reports a single-center, single-surgeon experience of eversion carotid endarterectomies (CEA) and factors associated with increased perioperative bleeding complications, including re-exploration for bleeding. The study concludes that preoperative treatment with clopidogrel, when used either alone or combined with aspirin was associated with an increased incidence of bleeding.
…”
mentioning
confidence: 99%